2013
DOI: 10.5812/cardiovascmed.10781
|View full text |Cite
|
Sign up to set email alerts
|

Effect of angiotensin ii type 1 receptor antagonist, losartan on inflammatory factor in atherosclerotic rabbits

Abstract: Background:Atherosclerosis is a progressive disease characterized by the accumulation of lipids and fibrous elements in the large arteries which now has become the pre-eminent health problem worldwide.Objectives:To investigate the effect and mechanism of Losartan intervention on atherosclerosis in rabbits fed with high-cholesterol diet.Materials and Methods:32 New Zealand rabbits were randomly divided into three groups: control group, high-cholesterol group and Losartan group. The level of weights, serum lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Our data demonstrate that in the in vivo model Ang II could aggravate a permeability increase, suggesting that interstitial edema might be facilitated in conditions triggering the increase in Ang II levels. Or data support the observations that Ang II is able to stimulate adhesion molecules able to promote leukocyte rolling and adhesion to endothelial cells [ 37 , 44 ].…”
Section: Discussionsupporting
confidence: 88%
“…Our data demonstrate that in the in vivo model Ang II could aggravate a permeability increase, suggesting that interstitial edema might be facilitated in conditions triggering the increase in Ang II levels. Or data support the observations that Ang II is able to stimulate adhesion molecules able to promote leukocyte rolling and adhesion to endothelial cells [ 37 , 44 ].…”
Section: Discussionsupporting
confidence: 88%
“…These observations suggest that AT 1 R antagonists may retard the process of thrombus formation by inhibiting platelet aggregation. [ 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Zhao et al () suggested remissions of inflammation and apoptosis as potential mechanisms mediating the therapeutic effects of irbesartan on atherosclerosis. Xu et al () reported that the effect of losartan on atherosclerosis is related to inhibiting inflammatory process but not lipid metabolism. In another study, losartan exerted an antiatherogenic effect on nonhuman primates possibly through protection of LDL from oxidation as well as suppression of vascular monocyte activation and recruitment factors (Strawn et al, ).…”
Section: Ras Pharmacological Inhibitors In the Treatment Of Inflammat...mentioning
confidence: 99%